Compound heterozygosity for KLF1 mutations associated with remarkable increase of fetal hemoglobin and red cell protoporphyrin - Satta, S.; Perseu, L.; Moi, P.; Asunis, I.; Cabriolu, A.; Maccioni, L.; Demartis, F. R.; Manunza, L.; Cao, A.; Galanello, R. (Haematologica (Roma), 2011)
The persistence of high fetal hemoglobin level in adults may ameliorate the clinical phenotype of beta-thalassemia and sickle cell anemia. Several genetic variants responsible for hereditary persistence of fetal hemoglobin, linked and not linked to the beta globin gene cluster, have been identified in patients and in normal individuals. Monoallelic loss of KLF1, a gene with a key role in erythropoiesis, has been recently reported to be responsible for persistence of high levels of fetal hemoglobin. In a Sardinian family, high levels of HbF (22.1-30.9%) were present only in compound heterozygotes for the S270X nonsense and K332Q missense mutations, while the isolated S270X nonsense (haploinsufficiency) or K332Q missense mutation were associated with normal HbF levels (<1.5%). Functionally, the K332Q Klf1 mutation impairs binding to the BCl11A gene and activation of the γ- and β-globin promoters. Moreover, we report for the first time the association of KLF1 mutations with very high levels of zinc protoporphyrin.